Social Contexts and Gender Disparities in Students’ Competence Beliefs: The Role of Gender-Stereotypical Beliefs and Achievement Patterns in the Classroom for Students’ Self-Concept in Gender-Stereotypical Subjects - Andersen, Ida G.; Smith, Emil (Frontiers in Education, 2022)
This study investigated the role of social contexts for gender disparities in education by examining the associations between gender-stereotypical beliefs (GSB) of students, peers and teachers and gender achievement patterns in the classroom and students’ self-concept in language and math. We applied multilevel models with school fixed effects to a unique sample of combined survey and register data from Denmark to analyze detailed learning environments within schools and their correlations with gender differences in self-concept across subject domains. Results showed a gender gap in favor of boys in mathematics net of academic achievement that were consistent across classrooms. In language, the influence of gender varied across classrooms. Furthermore, although GSB and gender achievement pattern did not alter the gender gap in either language or mathematics, we found that they moderated the relationship between gender and self-concept in heterogeneous ways across subjects. While teachers’ GSB increased the gender gap in language by decreasing boys’ self-concept, students’ own GSB were more important for students’ self-concept in mathematics. Moreover, girls’ mathematics self-concept was lower in classrooms in which female peers had a relatively higher level of mathematics achievement compared to boys, suggesting that counter-stereotypical achievement patterns in the classroom do not increase students’ self-concept in subjects with strong gender stereotypes. On the contrary, girls are most likely to compare themselves to female peers, resulting in a negative association with self-evaluations. Our results highlighted the role played by social contexts in schools in the generation of gender differences in self-concept in traditionally stereotyped subject domains, but also showed important differences in how boys and girls were affected by their learning environments across different subject domains, suggesting there are different mechanisms at play.